Status of Human-wildlife Conflict and Mitigation Strategies in Marwahi forest Division, Bilaspur Chhattisgarh - Akhtar, Naim; Chauhan, N. P. S. (Indian Forester, 2008)
Marwahi Forest Division is well known for human-sloth bear conflict. Available forest cover is highly degraded, fragmented and interspersed with agricultural crop fields, and small townships. Data since 1990 onwards reveal 28 cases of human death by wild animals, comprising of 13 men and 15 women. Except 2, all casualties were caused by sloth bear. 801 incidences of human mauling comprised of 591 men and 210 women were registered by Forest Department. A maximum of 528 incidences of mauling were caused by sloth bear followed by 220 and 53 by jackals and other wild animals respectively. Range of incidences per month varied from 51-93 with a mean 66.8 Â± 14.8. In Marwahi range 72.5% incidences of human mauling occurred in village area followed by 18.5% and 9.0% in forest and house respectively. Altogether 1453 incidences of livestock lifting were recorded in Marwahi forest division. No major changes were observed in extent of biotic pressure. However, extraction of stones from bear den sites has increased considerably. People need to be educated and made aware of ecology, feeding habits, movement and behaviour of problematic animals such as sloth bear, jackal, hyena and leopard through seminars and workshop so that people can avoid confrontation and play an active role in conservation. Livestock should be properly protected by villagers in enclosures made up of rubble wall. Sloth bear population has declined by 40% during last six years so there is a need to monitor the status of sloth bear population in the area.